(untitled) (Journal of the College of Basic Education, 2024)
Theoretical results have been based on the current experimental data published in EXFOR library in international Atomic Energy Agency (IAEA) described in detail for the thermal neutron induced fission cross sections with their error in a systematic manner of U-237 and Np-237. These data reviewed and analyzed. An estimate of neutron induced fission spectrum weighted average cross sections are their respective errors of the available data preformed with a Matlab-8.0 by install a recom.m program . The authors aims of this work have been attempt, thorough statistical evaluation of existing a recommended thermal neutron fission cross sections for U-237 and Np-237 in the energy range between their respective thresholds up to 24.9MeV for U-237 and up to 19.9MeV for Np-237. The purpose of this work is to combine the recommended cross sections with recommended (n,f) cross sections of contamination Np-237 which is the daughter of U-237. The contamination contribution has been added by the in growth factor 25%, 50%, 75%, 100% from the reaction. The recommended (n,f) cross section have been averaged for U-237 and U-235 the value obtain for the ratio is 0.6971 which is agreement with the value 0.62 obtained by McNally et al.. The spin effect term has been discussed in the binding energy calculations. The relative neutron flux for U-237 is in comparable with that for Np-237 neutron fission cross sections.